2017
DOI: 10.1136/bmjresp-2017-000178
|View full text |Cite
|
Sign up to set email alerts
|

Sound: a non-invasive measure of cough intensity

Abstract: IntroductionCough intensity is an important determinant of cough severity reported by patients. Cough sound analysis has been widely validated for the measurement of cough frequency but few studies have validated its use in the assessment of cough strength. We investigated the relationship between cough sound and physiological measures of cough strength.Methods32 patients with chronic cough and controls underwent contemporaneous measurements of voluntary cough sound, flow and oesophageal pressure. Sound power,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
(20 reference statements)
1
36
1
1
Order By: Relevance
“…One study has demonstrated even the use of a nose-clip influences cough sounds (24). Of note the correlations observed in this study significantly differ from a previous publication where cough sounds were studied when patients coughed into a facemask, additionally in that study participants were also trained to produce coughs which generated oesophageal pressures targeted within specific quintiles of maximum pressure, hence also somewhat artificial circumstances (15) Currently, there is no accepted definition of cough intensity and although the perception of cough intensity is likely to include both social and psychological factors (4), the mechanical aspects of coughing are likely to feature highly. This study suggests that whilst cough sounds are related to the physiological processes during cough, the correlations observed in this study are overall weak and therefore sound is unlikely to be able to discriminate between coughs associated with greater EMG activity or pressure, parameters which are most likely to be important components of perceived cough intensity.…”
Section: Accepted Manuscriptcontrasting
confidence: 81%
See 1 more Smart Citation
“…One study has demonstrated even the use of a nose-clip influences cough sounds (24). Of note the correlations observed in this study significantly differ from a previous publication where cough sounds were studied when patients coughed into a facemask, additionally in that study participants were also trained to produce coughs which generated oesophageal pressures targeted within specific quintiles of maximum pressure, hence also somewhat artificial circumstances (15) Currently, there is no accepted definition of cough intensity and although the perception of cough intensity is likely to include both social and psychological factors (4), the mechanical aspects of coughing are likely to feature highly. This study suggests that whilst cough sounds are related to the physiological processes during cough, the correlations observed in this study are overall weak and therefore sound is unlikely to be able to discriminate between coughs associated with greater EMG activity or pressure, parameters which are most likely to be important components of perceived cough intensity.…”
Section: Accepted Manuscriptcontrasting
confidence: 81%
“…A few authors have also investigated cough sound intensity which, as expected, is correlated with the flow responsible for generating the sound (13,15). Cough effort has also been shown to influence cough sounds (16,17) but again the impact of cough operating volume was not taken into account in these studies and low operating volume coughs, where flow is…”
Section: Accepted Manuscript 1 2 Introductionmentioning
confidence: 94%
“…Moreover, it was shown that the flow profile of inhalations can be estimated based on the logarithmic relationship between the acoustic envelope of the inhalation sound and the flow volume [28]. In contrast, a strong linear correlation between cough sound and cough flow has also been reported [36]. Our study revealed a nonlinear relationship between cough sound and cough flow.…”
Section: Discussionmentioning
confidence: 58%
“…Cough intensity can be measured via audio [28], however, this approach has limited feasibility in real-world, out-patient scenarios. A vibrometer-based approach surmounts these obstacles and allows additional features like cough episode peak and power to be reliably…”
Section: Discussionmentioning
confidence: 99%